On the historiography of the language question in post-1974 Greece - Patrikiou, Alexandra (Historein, 2017)
The works of Alexis Dimaras, Rena Stavridi-Patrikiou and Anna Frangoudaki have undeniably shaped, each in a different way but positively all together, the framework within which the historiography of the language question evolved since the early years of the Metapolitefsi, as the post-dictatorship period is known in Greece. Commenting on the different interpretations and exposing main convergences and divergences between these works, one will be able to contemplate their contributions to historiography and to scholarly thought in general. The aim of this paper is to examine these works as products of their time and to demonstrate how in a period of transitions and ideological redefinitions a renewed relation to the past may have been developed.